2014
DOI: 10.1152/ajprenal.00069.2014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of angiotensin II-induced inflammatory cytokines by the Epac1-Rap1A-NHE3 pathway: implications in renal tubular pathobiology

Abstract: Besides the glomerulus, the tubulointerstitium is often concomitantly affected in certain diseases, e.g., diabetic nephropathy, and activation of the renin-angiotensin system, to a certain extent, worsens its outcome because of perturbations in hemodynamics and possibly tubuloglomerular feedback. Certain studies suggest that pathobiology of the tubulointerstitium is influenced by small GTPases, e.g., Rap1. We investigated the effect of ANG II on inflammatory cytokines, while at the same time focusing on upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Remarkably, ANG II-mediated expression of proinflammatory cytokines could be blocked by a NHE3 inhibitor S3226 or with EPAC1 and PKA activators. These data reveal a novel EPAC1-Rap1A-NHE3 pathway that mediates ANG II-induced cytokine production in kidney epithelial cells and may have important implications in tubulointerstitial pathobiology relevant to various renal diseases (1137).…”
Section: Epac Protein and Na ϩ /H ϩ Exchangersmentioning
confidence: 85%
“…Remarkably, ANG II-mediated expression of proinflammatory cytokines could be blocked by a NHE3 inhibitor S3226 or with EPAC1 and PKA activators. These data reveal a novel EPAC1-Rap1A-NHE3 pathway that mediates ANG II-induced cytokine production in kidney epithelial cells and may have important implications in tubulointerstitial pathobiology relevant to various renal diseases (1137).…”
Section: Epac Protein and Na ϩ /H ϩ Exchangersmentioning
confidence: 85%
“…Recent studies have shown that the activation of various inflammatory molecules, such as cytokines (IL-6, IL-8, IL-1b, and TNF-a) [24], adhesion molecules (ICAM-1) [25], chemokines (MCP-1) [26], synthetase (iNOS and COX-2), and growth factors (VEGF, TGF-b) [27] contribute to the progression of DN. In our study, LPS up-regulated the production of a spectrum of inflammatory molecules in hRPTECs, including IL-6, IL-8, IL-1b, TNF-a, iNOS, COX-2, MCP-1 and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Key players in this cascade include TGF-␤1 and various mediators of inflammation, involving several cell types in the kidney, as well as leukocytes and other immune cells. It is also interesting to note that an NHE3 inhibitor, S3236, reduces ANG II-stimulated induction of several cytokines in cultured proximal tubular cells (1172), suggesting a close relationship between renal inflammation and enhanced sodium reabsorption.…”
Section: Renal Fibrosis and Inflammationmentioning
confidence: 99%